Grading of Aortic Stenosis: Is it More Complicated in Women? - Dana Cramariuc; Edda Bahlmann; Eva Gerdts (European Cardiology Review)
Aortic stenosis (AS) is the most common valvular heart disease and the main indication for valvular replacement in older women. Correct AS grading is mandatory for an adequate selection of patients for both surgical and transcatheter aortic valve replacement. Women and men have different AS severity grades at the same level of aortic valve calcification. Moreover, besides having smaller cardiac volumes, left ventricular outflow tract and aortic size, women have a specific pattern of left ventricular structural and functional remodelling in response to the AS-related chronic pressure overload. Here, the sex-specific cardiac changes in AS that make AS grading more challenging in women, with consequences for the management and outcome of this group of patients, are reviewed.